Putting the Humanities PhD to Work : Thriving in and beyond the Classroom - Rogers, Katina L. (Book collections on Project MUSE., 2020)
"PUTTING THE HUMANITIES PHD TO WORK rethinks the purpose and employment potential of humanities doctoral recipients. As the number of tenure-track faculty lines decrease, and more universities turn to under-paid and contingent adjunct instructors to teach their courses, it may seem like a gamble for someone to enter a doctoral program. But as Katina Rogers points out, doctoral programs are only a gamble if one sees tenure track faculty positions as the only legitimate employment option for humanities PhDs. Instead, Rogers argues that as tenure-track lines decrease-not, as she finds, because of an overabundance of doctoral recipients, but rather because of university austerity measures-the academy must rethink what postgraduate "success" looks like. Rogers posits that removing the premium-both professionally and culturally-on achieving tenure-track positions would allow for a more expansive view of what doctoral training in the humanities can achieve. Drawing on her own experience as a humanities PhD who forged a career outside of tenure-track academia, Rogers's book is guided by, and seeks to answer, two questions: What can be done to normalize a wider range of career pathways for humanities PhDs? And how might a more expansive view of what designates postgraduate "success" help improve the humanities and benefit the public? Chapter 1, which focuses on the academic labor market, examines universities' reliance on adjunct faculty positions, and investigates why tenure-track faculty positions have become increasingly difficult to obtain. Chapter 2 examines how current university practices perpetuate systems of inequality that result in the underrepresentation of women and genders of all races and ethnicities in the academy. Chapter 3 explores work-such as digital dissertations, policy research, and activist engagement- that expands scholarship beyond the university. Chapter 4, which is addressed to faculty advisors and program directors, offers guidance on how advisors can mentor graduate students to consider a wider range of employment pathways, as well as suggestions for more long-term department and program reforms. Chapter 5, addressed to graduate students, offers case studies and suggestions for planning careers outside of the academy. This book will be of interest to graduate students, graduate student advisors, as well as scholars of higher education and critical university studies"--